2015
DOI: 10.4331/wjbc.v6.i3.148
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic interplay between glycolysis and mitochondrial oxidation: The reverse Warburg effect and its therapeutic implication

Abstract: Aerobic glycolysis, i.e. , the Warburg effect, may contribute to the aggressive phenotype of hepatocellular carcinoma. However, increasing evidence highlights the limitations of the Warburg effect, such as high mitochondrial respiration and low glycolysis rates in cancer cells. To explain such contradictory phenomena with regard to the Warburg effect, a metabolic interplay between glycolytic and oxidative cells was proposed, i.e. , the "reverse Warburg effect". Aerobic glycolysis may also occur in the stromal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 191 publications
1
122
0
Order By: Relevance
“…Cancer cells preferentially utilize glycolytic metabolism to produce ATP, even in the presence of oxygen, a phenomenon termed aerobic glycolysis (6,7). Inhibition of glycolysis has been suggested to improve the outcomes for cancer therapy (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells preferentially utilize glycolytic metabolism to produce ATP, even in the presence of oxygen, a phenomenon termed aerobic glycolysis (6,7). Inhibition of glycolysis has been suggested to improve the outcomes for cancer therapy (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of this aberrant phenomenon of aerobic glycolysis in cancer cells has led to novel tumor therapeutic strategies targeted at switching back to mitochondrial oxidative phosphorylation and there by leading to cancer cell death [26]. Several compounds have been reported to suppress the growth of tumor cells by affecting aerobic glycolysis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds have been reported to suppress the growth of tumor cells by affecting aerobic glycolysis [26]. Three key rate limiting enzymes in aerobic glycolysis are: hexokinase, pyruvate kinase (PK) and lactate dehydrogenase (LDH) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida, in 2015, showed that tumours expressing high levels of MCT4 do no exhibit the reverse Warburg effect [55]. The microenvironment of cancer is ever changing, and cancer cells can and do vary in their metabolic phenotype even within the same tumour mass [56]. Although hard to generalise in solid tumours with a hypoxic core, perhaps the Warburg effect most probably predominates with reduced oxygen levels driving the cells to make the most of all available glucose.…”
Section: Positron Emission Tomography Imaging and The Reverse Warburgmentioning
confidence: 99%